Energy saving intermittent electro-Fenton system combined with commercial MoS2 for effective Rhodamine B degradation. (20th March 2021) - Cui, Yanping; Zhou, Zhengwei; Gao, Ya; Lei, Lidan; Cao, Jungang; Wu, Ruojie; Liang, Lili; Huang, Zhaoqiang
Abstract: Without external O2 supply and solution pH adjusting, commercial molybdenum sulfide (MoS2 ) was firstly applied as co-catalyst in intermittent electro-Fenton process for Rhodamine B (RhB) degradation. In this energy saving system, Fe 2+ /Fe 3+ conversion was facilitated and H2 O2 activating was accelerated by MoS2 . Granular activated carbon wrapped with stainless steel mesh (GACSS) was used as cathode, from which, H2 O2 and iron sources were in-situ generated. With 0.1 g/L MoS2, and 50 mA applied current with 10 min on-10 min off power frequency, RhB degradation rate constant in the MoS2 intermittent electro-Fenton was approximately 2.4 times as that without MoS2 system. Quenching experiments, electron spin resonance (ESR) characterization and free radical fluorescence tests demonstrated hydroxyl radicals (·OH) was the dominant reactive species, and the superiority of intermittent electrolysis mode for RhB degradation. During power on, H2 O2 was constantly generated on cathode. In electricity interval, Fe 2+ /Fe 3+ conversion was accelerated on the active sites (Mo 4+ ) to activate residual H2 O2 and more ·OH was generated to RhB degradation. Additionally, the characterization analysis (XPS, SEM and FT-IR) demonstrated MoS2 and GACSS cathode exhibited excellent catalytic and chemical stability in recyclability. Low-cost multifunctional cathode with a high efficiency co-catalyst was combined in this energy saving electro-Fenton operating system for RhB degradation. Graphical abstract: Image 1 Highlights: MoS2 as co-catalyst accelerated the conversion of Fe 2+ /Fe 3+ and greatly enhanced the degradation performance in intermittent GACSS EF. The intermittent power on-off mode presented excellent energy saving in MoS2 GACSS system. The catalytical mechanism of MoS2 in GACSS EF system was analysed.